Adverse Events Related to Accidental Unintentional Ingestions From Cough and Cold Medications in Children. Issue 1 (23rd June 2020) - Wang, George Sam; Reynolds, Kate M.; Banner, William; Bond, G. Randall; Kauffman, Ralph E.; Palmer, Robert B.; Paul, Ian M.; Rapp-Olsson, Malin; Green, Jody L.; Dart, Richard C.
Abstract : Objectives: Previous research has demonstrated that accidental unsupervised ingestions (AUIs) were responsible for the majority of cough and cold medication (CCM) ingestions leading to significant adverse events (AEs) in children. The objective of this analysis was to characterize the role of AUIs in the morbidity associated with CCM exposure in children. Methods: This surveillance study collected data from 5 United States data sources from 2009 to 2016, in children younger than 6 years with an AE from an AUI involving at least 1 CCM over-the-counter pharmaceutical ingredient. An expert panel reviewed each case to determine causality. Results: From 4756 total cases reviewed, 3134 (65.9%) had an AE from an AUI determined to be at least potentially related to a CCM ingredient. The majority (61.3%) of cases occurred in children aged 2 to younger than 4 years. Most exposures occurred in the child's own residence (94.9%), and 43.8% were admitted to a health care facility (22.0% to a critical care unit). Dextromethorphan and diphenhydramine, when packaged alone or in combination products, contributed to 96.0% of AUIs. The most common specific products involved were single-ingredient pediatric liquid diphenhydramine (30.1%) and single-ingredient pediatric liquid dextromethorphan (21.4%). There were 3 deaths from solid diphenhydramine formulations. Conclusions: There continues to be opportunities for the implementation of interventions to prevent AUIs of CCM in children. Additional emphasis on engineering controls, such as flow restrictors for liquid formulations targeting diphenhydramine and dextromethorphan products, represent additional opportunities to further reduce AEs from AUIs of CCM.